Sleep during menopausal transition: a 10-year follow-up. Issue 6 (16th December 2020) - Kalleinen, Nea; Aittokallio, Jenni; Lampio, Laura; Kaisti, Matti; Polo-Kantola, Päivi; Polo, Olli; Heinonen, Olli J; Saaresranta, Tarja
Abstract: Study Objectives: A 10-year observational follow-up study to evaluate the changes in sleep architecture during the menopausal transition. Methods: Fifty-seven premenopausal women (mean age 46 years, SD 0.9) were studied at baseline and after a 10-year follow-up. At both time points, polysomnography (PSG) was performed, and the serum follicle-stimulating hormone (S-FSH) concentration was measured. Linear regression models were used to study the effects of aging and menopause (assessed as change in S-FSH) on sleep. Results: After controlling for body mass index, vasomotor, and depressive symptoms, higher S-FSH level was associated with longer sleep latency (B 0.45, 95% confidence interval [CI]: 0.07 to 0.83). Aging of 10 years was associated with shorter sleep latency (B −46.8, 95% CI: −77.2 to −16.4), shorter latency to stage 2 sleep (B −50.6, 95% CI: −85.3 to −15.9), decreased stage 2 sleep (B −12.4, 95% CI: −21.4 to −3.4), and increased slow-wave sleep (B 12.8, 95% CI: 2.32 to 23.3) after controlling for confounding factors. Conclusions: This study suggests that PSG measured sleep of middle-aged women does not worsen over a 10-year time span due to the menopausal transition. The observed changes seem to be rather age- than menopause-dependent.